Book transit shelter : a method in developing a zero-waste environment and healthy campus community / Muhammad Naim Mahyuddin ...[et al.] - Muhammad Naim, Mahyuddin; Hafizah, Mohd Latif; Muhammad Redza, Rosman; Noor Sahidah, Samsudin; Rafizah, Mohamed Nordin (2015)
The production of a new book requires raw materials to be extracted from the earth, published, and transported. This process uses enormous amounts of material and energy. One way to save natural resources, protect the environment, and most importantly save money is by reusing items that are utilizable. The Book Transit System is created to minimize the waste of books being thrown away, especially by final semester students of Universiti Teknologi MARA, Perak. In addition, it encourages knowledge-sharing within the community. The book transit system is designed so that it can be attached to almost any solid surface and is user-friendly. While the design of this system is flexible and varies, for the purpose of this study, a Book Transit Shelter has been created. An existing shelter in the campus is utilized where a glass box, complete with steel book lift-up handle is attached to the shelter. Students and/or members of the community who walk by can just drop in any size of book in the glass box. As the glass is transparent, other students are able to have a quick look at the donated books. If they are interested, they can simply lift the handle and pick up the book they want for free. This concept is adapted from the zero-waste concept, but enriched with altruism and green environmental principles.